(untitled) (Journal of Organizational Psychology, 2022)
This article explores how a culture of strengths-based leadership can positively impact professional development for school site administrators. The strengths of school district administrators were measured through the administration of CliftonStrengths™ assessment. Themes that emerged were determined through the assessment and qualitative analysis of responses. A sample of convenience 50 principals and assistant principals from a public school district in Southern California participated in this research. The findings revealed that the common talent themes among school site administrators were relationship building, executing, influencer, and learner. This study supports future practices to enable human resources personnel to design targeted professional development for school site administrators. An analysis of a school administrator’s strengths and personality traits is unique to each school district. The results support human resource professionals’ efforts to determine personnel’s future needs, including hiring and developing school leaders.